A Qualitative Study of Use of Mindfulness to Reduce Long-Term Use of Habit-Forming Prescription Drugs - Dundas, Ingrid; Ravnanger, Kari; Binder, Per-Einar; Stige, Signe Hjelen (Frontiers in Psychiatry, 2020)
Objective: The aim of this study was to study the utility of a mindfulness-based relapse prevention program for reducing long-term use of habit-forming prescription drugs. We explored participant-perceived outcomes with a particular focus on their post-intervention strategies for controlling medication intake. Method: Eighteen participants provided semi-structured qualitative interviews shortly after completion of the program and 13 participants were also interviewed one year after completion. Participants were asked about the conditions that originally led to use of medication, how they had attempted prior to the course to cope with problems associated with these conditions and their prescription drug-use, and whether and how their coping strategies had changed after participation in the program. Thematic analysis was performed within the framework of a realist epistemology, with an emphasis on researcher reflexivity. Results: The following themes were identified in the material: Increased present-moment sensory awareness, Observing without controlling, Self-acceptance, Making conscious choices, Non-judgmental self-guidance, Sense of control and Challenges of learning and using mindfulness. Although these findings are closely related to the specific needs of our sample mainly coping with tapering use of prescription drugs they are largely in line with existing research on mindfulness interventions. An exception is the theme “Non-judgmental self-guidance”, which encompasses change in individuals’ inner dialogue and practical self-care. Conclusions: Analyses suggested that MBRP might increase individuals’ control over medication intake by shifting individuals’ attention towards present-moment sensory awareness of concrete stimuli, thereby facilitating other kinds of control, such as non-judgmental inner self-guidance and more adaptive ways of reducing distress. We suggest that it is the moment-to-moment sensory awareness and non-controlling observation of distress, together with inner self-guidance, that differentiates mindful control from dysfunctional attempts at direct, top down control via preservative negative cognition (thought suppression and self-blaming) and unwanted use of medication.